2010
DOI: 10.1007/s00006-010-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Exact Description of Rotational Waves in an Elastic Solid

Abstract: Abstract. Conventional descriptions of transverse waves in an elastic solid are limited by an assumption of infinitesimally small gradients of rotation. By assuming a linear response to variations in orientation, we derive an exact description of a restricted class of rotational waves in an ideal isotropic elastic solid. The result is a nonlinear equation expressed in terms of Dirac bispinors. This result provides a simple classical interpretation of relativistic quantum mechanical dynamics. We construct a Lag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…14 It has also been shown that rotational waves in an isotropic continuous elastic solid can be described within the formalism of the Dirac equation providing a classical interpretation of relativistic quantum mechanics. 15 Conical Dirac dispersions or Dirac-like behavior in photonic crystals (the electromagnetic wave counterpart of PC) [16][17][18][19] and PC 20,21 have also recently received attention. Longhi 22 and Ref.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has also been shown that rotational waves in an isotropic continuous elastic solid can be described within the formalism of the Dirac equation providing a classical interpretation of relativistic quantum mechanics. 15 Conical Dirac dispersions or Dirac-like behavior in photonic crystals (the electromagnetic wave counterpart of PC) [16][17][18][19] and PC 20,21 have also recently received attention. Longhi 22 and Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Now, by employing the exchange of variables as 2(α + µ) u α −→ u α and e/ 2(α + µ) −→ e, (38) 8 The comparison of fermions and rotation waves has also been considered in Refs. [14][15][16]. Besides, the anticommutation nature of spinor field (27) has been described in Ref.…”
Section: Qed Treatmentmentioning
confidence: 98%
“…The Three Wave Hypothesis by Horodecki, which is based on de Broglie's particle-wave duality, and the assumption of covariant aether [14,15] are also consistent with QQM. Close demonstrated a description of rotational waves in an elastic solid as the spin equivalent [16][17][18].…”
Section: Introductionmentioning
confidence: 99%